A Secured Case Management System for Al-Tayba Court - Sakher Taher Mohammaad Al-Sheyyab
With the rapid development of Informational Communication Technology (ICT) and its entry in various aspects of human life, it is necessary to invest in this modern technology due to its great benefits in data protection, time saving, reducing efforts and money costs. In Jordan, the current tradisional court system is unable to solve the problems of securing cases records, classification of cases and manual searching for court files. Therefore, the objectives of this study are to identify the key requirements for developing a secure electronic case management system for Al-Tayba court in Jordan and to evaluate the usability and ease of use of this system. This applied Research Design Methodology ( Vaishnavi & Kuechler, 2008) and also adopted IBM security framework to emphasize the security aspects. The results show the proposed system successes to handle the working activities of the employees efficiently, and the users accept the proposed system as new solution to avoid the challenges of the current system. In this study, the case management system is believed to contribute in developing solutions for the current problems at the tradisional courts. These solutions are data security, saving time, efforts, and money and increasing the efficiency of court actors. It is hoped that this system will facilitate the electronic process of cases management in Al-Tayba court in Jordan.